Analysis and generalization of the experience of implementing a system for training and retraining personnel in the field of energy and resource saving - Kanuk, G.; Antonenko, N.; Prokopenko, O. (Problems of Engineer-Pedagogical Education, 2021)
The article considers the important and topical issues of energy and resource saving in the various aspects of scientific and pedagogical activity. The main directions related to the obtained scientific results implementation on the relevant practical markets of the intellectual products have been developed and substantiated. The relevance of the creation and implementation of a system for training and retraining of personnel in the field of energy and resource conservation is justified. The main components of the organization scheme of a complex continuous system of education and upbringing in the sphere of energy and resource saving are presented. The universal generalized technological process of training is presented in the form of integral functional, to which minimization the task of developing optimum contents of training courses is reduced. The corresponding generalized learning content model is presented. The structural-functional model of training future engineers and teachers in the discipline "Fundamentals of energy and resource saving" is given. The rational sequence and interconnection of the acquisition of basic knowledge and skills in the discipline "Fundamentals of energy and resource conservation are shown. In accordance with the proposed model, a functioning sample of a universal laboratory base was created using the original computerized stands, and also methodological support kits were developed for the course "Fundamentals of energy and resource saving" taught in education institutions of various levels. The paper presents a scheme to group specializations of the specialty "Vocational Education" (by specializations) using processes types in the technological equipment as well as the universal scheme of the energy losses in the physical processes used in various technological cycles. The main results of contractual, state budget and student research projects on key problems of the education and training system in the field of energy and resource saving are given. The work results have been published in a number of scientific articles, monographs and patents. Thus, the article formulates a generalized representation of the scientific, technical and scientific-pedagogical results which were obtained by the authors in the process of creating and implementing the project for the system of training and professional development of personnel in the energy and resource saving industry.